Writing dance a study of motif writing as a dance instructional method. - Torres, Marie Yvonne Teodoro
The principal objective of this study was to investigate or assess the effect of using Motif in teaching dance making. This study also aimed to search for a better approach in teaching dance, to be able to provide general ideas or knowledge on how to improve one's teaching and to help teachers and students to communicate with each other more effectively that would result to better understanding and development of the students.